Cluster After 20 Years of Operations: Science Highlights and Technical Challenges. Issue 8 (4th August 2021) - Escoubet, C. P.; Masson, A.; Laakso, H.; Goldstein, M. L.; Dimbylow, T.; Bogdanova, Y. V.; Hapgood, M.; Sousa, B.; Sieg, D.; Taylor, M. G. G. T.
Abstract: The Cluster mission was the first constellation using four identical spacecraft to study Sun‐Earth connection plasma processes. Using four spacecraft in a tetrahedron shape, it could measure, for the first time, 3D quantities such as electrical currents, plasma gradients or divergence of the electron pressure tensor and 3D structures such as boundaries, surface waves or vortices. Launched in pairs in July and August 2000, on two Soyuz rockets from Baikonur, the four spacecraft have been collecting data continuously for more than 20 years. The mission faced many challenges during the years of operations as some spacecraft subsystems had a lifetime of a few years beyond the initial two‐year mission. The major one was to operate without functioning batteries and to successfully pass short and long eclipses, up to 3 h long, without damaging the on‐board computers and transmitters and without freezing the fuel. More than 1, 000 eclipses have been successfully passed since 2010 using a specially made procedure which switches off the complete spacecraft before entering into eclipse and switches it on when the Sun is again illuminating the solar panels. During 20 years, many discoveries and science results have been published in more than 2, 700 scientific papers. A few highlights are presented here, focusing on how varying the spacecraft separation was essential to achieve the science goals of the mission. The Cluster Science Data System and the Cluster archive allows public access to all science data as well as spacecraft ancillary data. Key Points: Selected science results achieved by Cluster are presented Operation of the mission for 20 years, challenges and technical difficulties are reported Science is enhanced by combining with other constellations and by making all Cluster data available to the public